Definition of contact stress in friction units on the basis of the acoustic emission method - Sergay Filonenko; Viacheslav Stadnychenko; Anzhelika Stakhova (Aviation, 2009)
The following results of acoustic emission signals researches were obtained during the change in contact stress. It is shown that the theoretical regularity of change in average level of the acoustic emission resulting signal at contact stress has a linear character. Analogical regularity is received during experimental researches. It is showed that the sensitivity of the acoustic emission method and the precision of determining contact stresses are considerably better, than the tensometry method. The recording of the moment when friction unit seize begins is also considerably more precise.